Feasibility and usefulness of three-dimensional optical coherence tomography guidance for optimal side branch treatment in coronary bifurcation stenting. (1st January 2018) - Nagoshi, Ryoji; Okamura, Takayuki; Murasato, Yoshinobu; Fujimura, Tatsuhiro; Yamawaki, Masahiro; Ono, Shiro; Serikawa, Takeshi; Hikichi, Yutaka; Nakao, Fumiaki; Sakamoto, Tomohiro; Shinke, Toshiro; Kijima, Yoichi; et al.
Abstract: Background: For the treatment of coronary bifurcation lesions, optimal guidewire (GW) recrossing after main vessel stenting is important for good stent apposition at the side branch (SB) orifice in kissing balloon inflation (KBI). Methods: We analyzed 150 bifurcation lesions treated with single stenting following KBI in the three-dimensional optical coherence tomography (3D-OCT) bifurcation registry study (2015–16) and a single center experience (2012–16). OCT examination was performed after GW recrossing to the SB and after KBI. Patients were divided into two-dimensional (2D, n  = 78) and 3D groups ( n  = 72) according to 2D- or 3D-OCT guidance. GW recrossing position, jailing configuration of the stent over the SB (divided into Link-connecting type: stent link connecting to the carina and Link-free type: no stent link at the carina) and stent apposition were compared between the groups. Results: Distal GW recrossing was achieved in 75.6% and 91.7% in the 2D and 3D groups, respectively ( P  = 0.004). Compared with the 2D group, the incidence of incomplete stent apposition (ISA) toward the SB in the 3D group tended to be lower in the whole cohort (14.5 ± 13.6% vs 10.0 ± 9.0%, P  = 0.077), and was significantly lower in left main trunk bifurcations (18.7 ± 12.8% vs 10.3 ± 8.9%, P  = 0.014). Independent contributors to ISA were the Link-connecting type (β 0.089, P  < 0.001), distal GW recrossing (β − 0.078, P  = 0.001), and age (β − 0.0020, P  = 0.012). Conclusion: Optimal GW recrossing under 3D-OCT guidance is feasible and improves stent apposition, which may lead to a better clinical outcome in the treatment of bifurcation lesions.